The Legal Nature of the Simple Joint Stock Company - Start-Ups Company - Bouamar, Sabrina; Boukharouba, Hamza (Journal of Legal Studies and Researches, 2023)
Startups emerging companies have become one of the most important engines of the contemporary economy. For this reason, the Algerian legislator issued Law 22-09 that established the simple joint-stock company as a new form of commercial company, which is exclusively for emerging enterprises, and the company combines the financial and personal character.